Waste Reduction for Hospital Cyclical Pharmaceutical Demand Forecasting Mean Squared Error Reduction - Mongkalig, Chatpon (Business Administration and Management Journal Review, 2026)
The objective of this research was to analyze the appropriate forecasting techniques for the case study hospital pharmaceutical products cyclical demand forecasting mean squared error reduction, and comparison between the proposed forecasting method and the current forecasting method of the case study hospital using Paired t-Test for the confirmation test. This research focused on the important pharmaceutical products using ABC analysis to identify class A, which the inventory value was more than 70 % with cyclical or seasonal demand (31 SKUs). Randomized complete block design (RCBD) was applied in the design of experiments in this research. According to the experimental results, the forecasting techniques had significant effects on the mean squared deviation (MSD). The most appropriate forecasting technique was Winters’ method with 12 months seasonal length. Mean squared deviation of the Winters’ method was significantly smaller than moving average with 3 months moving average length which was the forecasting method used by the case study hospital planners. The MSD of the proposed forecasting method decreased by 35.32 %.